ARSENIC MOBILITY IN THE AMBIENT SULFIDIC ENVIRONMENT: SORPTION OF ARSENIC(V) AND ARSENIC(III) ONTO DISORDERED MACKINAWITE - Wolthers M.; Charlet L.; van Der Weijden C.H.; van der Linde P.R.; Rickard D. (My University, 2005)
Arsenate, As(V), sorption onto synthetic iron(II) monosulfide, disordered mackinawite (FeS), is fast. As(V) sorption decreases above the point of zero surface charge of FeS and follows the pH-dependent concentration of positively charged surface species. No redox reaction is observed between the As(V) ions and the mineral surface over the time span of the experiments. This observation shows that As(V) dominantly forms an outer-sphere complex at the surface of mackinawite. Arsenite, As(III), sorption is not strongly pH-dependent and can be expressed by a Freundlich isotherm. Sorption is fast, although slower than that of As(V). As(III) also forms an outer-sphere complex at the surface of mackinawite. In agreement with previous spectroscopic studies, complexation at low As(V) and As(III) concentration occurs preferentially at the mono-coordinated sulfide edge sites. The Kd (L g−1) values obtained from linear fits to the isotherm data are ∼9 for As(V) and ∼2 for As(III). Stronger sorption of As(V) than As(III), and thus a higher As(III) mobility, may be reflected in natural anoxic sulfidic waters when disordered mackinawite controls arsenic mobility.